The sporophytic type of fertility restoration in the A3 CMS-inducing cytoplasm of sorghum and its modification by plant water availability conditions - L. A. Elkonin; V. V. Kozhemyakin; M. I. Tsvetova (Вавиловский журнал генетики и селекции)
The A3 type of CMS in sorghum is one of the most difficult to restore fertility because of the low frequency of fertilityrestoring genes among sorghum accessions, the complex mechanism of fertility restoration that occurs with the complementary interaction of two gametophytic genes Rf3 and Rf4, and the sensitivity of their expression to air and soil drought. In order to test the hypothesis of the sporophytic type of fertility restoration in CMS lines with A3 type cytoplasm developed in our laboratory, we analyzed segregation in the self-pollinated progeny of fertile F1hybrids grown under different water availability conditions (in a dryland plot, in plots with additional irrigation, in a growth chamber, and in an experimental field with a natural precipitation regime) and in their backcrosses to the maternal CMS-line. The presence of sterile plants in the F2 and BC1 families with the maternal CMS line grown in all tested water availability conditions argues for the sporophytic mechanism of fertility restoration. Cytological analysis of fertile F1 hybrids revealed a significant amount of degenerating pollen grains (PGs) with impaired starch accumulation and detachment of the PG contents from the cell wall. It is assumed that the expression of the fertility-restoring genes Rf3 and Rf4 in the hybrids with studied CMS lines starts already in the sporophyte tissues, normalizing the development of a certain part of the PGs carrying the recessive alleles of these genes (rf3 and rf4), which are involved in fertilization and give rise to sterile genotypes found in F2 and BC1 families. For the first time, the transgenerational effect of water availability conditions of growing a fertility-restoring line on male fertility of the F2 generation was detected: a pollinator grown in a plot with additional irrigation produced more fertile and less sterile individuals compared to the same pollinator grown under a rainfall shelter (p < 0.01), and the segregation pattern changed from digenic to monogenic, indicating heritable inhibition of the expression of one of the fertility-restoring genes (kind of “grandfather effect”). The possibility of selection for the stability of the fertility restoration system of the A3 cytoplasm to functioning under conditions of high vapor pressure deficit during the flowering period was shown. These data may contribute to the creation of effective fertility restoring lines for this type of CMS in sorghum.